Design with Nature on Cape Cod and the Islands - Ahern, Jack (John F.) (Book collections on Project MUSE., 2022)
"Cape Cod and the islands of Martha's Vineyard and Nantucket are special places known for their distinctive flora, including pine-oak forests, sandplain grasslands, and sand dunes peppered with bearberry shrubs. Unfortunately, this unique sense of place is under threat. In recent decades, contemporary landscape practices have come to depend on environmentally stressful fertilizers and irrigation systems, replacing this sensitive ecoregion's native flora with generic turfgrasses and popular commercial nursery trees and shrubs that could exist anywhere. Design with Nature on Cape Cod and the Islands seeks to reverse this damaging trend by offering landscape professionals, local officials, and homeowners a sustainable approach to landscape design based on the ecoregion's native plants and plant communities. Presenting detailed discussions of Cape Cod's natural history, Jack Ahern focuses on the principal plant communities that define its landscape character and that are well adapted to local soils and growing conditions, including climate change. The book also includes strategies for ecological planting design and a portfolio of photographs of active ecologically designed landscapes"--